EFFECT OF ROTATIONAL SPEED AND DWELL TIME ON PHYSICAL AND MECHANICAL PROPERTIES OF FRICTION STIR SPOT WELDING ALUMINIUM 1100 WITH ZN POWDER INTERLAYER ADDITION - Aditya Noor; Nurul Muhayat; . Triyono (Universitas Sebelas Maret, 2019)
Friction stir spot welding (FSSW) is one of the development of solid state welding to joint lightweight materials such as aluminium. In the automotive industry, lightweight materials are needed in the structure of vehicle construction to improve efficiency in vehicles. This research aims to find out how the effect of rotational speed and dwell time on physical and mechanical properties on the weld joint of aluminium 1100 with Zn interlayer addition. Variations used in rotational speed 1000, 1250, 1600 rpm and dwell time 6, 7, 8 s. Pullout fracture occur in tensile tests that are getting bigger with increasing rotational speed and dwell time. The results of SEM and EDS observations showed that the metallurgical bonded zone increased and kept the hook defect away. The spread of Zn in the stir zone area causes the formation of solid Al-Zn phase in a solid solution. The hook defect filled with Zn can minimize cracks that occur, so increased the tensile shear load. The highest tensile shear load value of FSSW AA1100 without Zn interlayer is 3.61 kN, while the FSSW AA1100 with Zn interlayer addition is 4.34 kN.